PENGUASAAN KOSAKATA BUDAYA LOKAL PADA SISWA SD DI LINGKUNGAN KAWASAN INDUSTRI KOTA SEMARANG - Subyantoro, - (Lembaran Ilmu Kependidikan, 2010)
The formulation of the problem to be studied in this small study were (1) how theclassification of the vocabulary of students in the industrial area, and (2) how thecharacteristics antarjenis comparison of vocabulary in the field of existing industriesin student essays? This study aims to obtain: (1) picture of the environment in theindustrial area students who live in the industrial area, (2) characteristics antarjeniscomparison of vocabulary in an existing industrial area on student essays. The sourcedata of this study is student writing an industrial theme. The paper was prepared byelementary school students with a number of words ranged from 100 to 250 words.Elementary school students who take the data were elementary school students inrural industries in the city of Semarang. Data collection technique is done throughrefer, interviews, and record. The tool used is the data card and questionnaire sheet.The results of this study indicate that the vocabulary of the field of industry tend to usethe students can be classified following: (1) industry-related vocabulary withindustrial activity, (2) industry-related vocabulary with the impact caused byindustrial activity, (3) vocabulary which the industrial field related to diseases causedby industrial activities, (4) vocabulary in addition to industry vocabulary.With a totalvocabulary of the industrys most widely used by students is the vocabulary that has anegative perception.Kata Kunci : kosakata, budaya lokal, kawasan industri